Natural and artificial consolidation of sand (beachrock) induced by cyanobacterial/algal mat photosynthesis - Yamaki, Katsunori; Yamamoto, Shoji; Kayanne, Hajime (Frontiers in Marine Science, 2025)
Beachrocks are naturally cemented coastal sediments found in the intertidal zones of subtropical and tropical coasts, serving as vital coastal barriers against erosion—a protection increasingly crucial in an era of rising sea levels. Despite extensive research, the mechanisms underlying beachrock formation remain unresolved. A leading hypothesis is that cyanobacterial and algal mat photosynthesis elevates calcium carbonate saturation in seawater, thereby facilitating carbonate precipitation. However, the extent to which algal activity alters seawater saturation states to drive precipitation is not well understood. To advance eco-technological applications for coastal protection, an in-depth understanding and replication of beachrock formation processes in laboratory settings are essential. In this study, we examined carbonate cement precipitation beneath natural beachrock driven by cyanobacterial/algal mat photosynthesis and successfully replicated this process in the lab. Field observations showed that photosynthesis increased pH from 8.18 to 9.43, raising the carbonate saturation state (Ω) from 3.4 to 9.9. In laboratory experiments, pH similarly rose from 7.69 to 8.47, elevating Ω from 3.1 to 6.0 under light conditions. In both settings, the subsequent decline in total alkalinity confirmed calcium carbonate precipitation. Indeed, after three months of incubation, the carbonate sediments consolidated by acicular aragonite cement—matching the morphology observed in natural beachrock—achieved a compressive strength of 3 MPa. While this strength may support beach stabilization, further improvements are needed to enhance mechanical durability for practical coastal defense—yet these findings represent a foundational step toward developing eco-technological methods for enhancing coastal resilience against sea-level rise.